The neurobiology of splitbrain crayfish - Barrera-Mera, Baltazar; Granados-Romero, Juan José; Vargas-Morales, José Juan; Barrera-Calva, Elvira; Banegas-Ruiz, Rodrigo; Pérez Ortega, Emilio; Barajas-Colón, José Ángel; Gómez-Mendoza, Francisco Fabian; Baca-Domínguez, Carlos Rubén; Caprielova, Yuri Jiménez; de la Rosa Llergo, Román Alberto; Mendoza-Aceves, Rodrigo; et al. (International Journal of Research in Medical Sciences, 2021)
Background: They crayfish brain is segmented into two symmetrical hemiganglia. Normally both hemiganglia are in direct communication through a series of well-defined neural bridges that cross de midline to form reciprocal cross connections. Methods: An original study was carried out in the Department of Physiology of the Faculty of Medicine, UNAM during the period from August 2019 to August 2020. 13 Crayfish Procambarus clarkii weighing between 1g to 30g were used. Each eyestalk of the animals was tied to a displacement transducer coupled with a polygraph so that optomotor or electrical activity was bilaterally recorded. The separation of the right from the left hemiganglia from the cerebral or supraesophageal ganglion was performed with a sagittal section, splitbrain (SB). Results: The normal photo motor reflex in crayfish eye is measured as a gradual decrease in the ERG amplitude. During tactile stimulation, the visual activation of both eyestalks in normal crayfish leads to a highly regular bilateral activity. The regular activity can only be altered by disturbing the mechanoreceptors located in the shell surrounding the eyestalks. Conclusions: The procedure presented in this article provides unique characteristics for the study of the nervous system such as a detailed response of the bilateral optomotor reflex.